Mg/S@g-C3N4 nanosheets: A promising fluorescence sensor for selective Cu2+ detection in water - Z.A. Alrowaili; Asmaa I. El-Tantawy; S.A. Saad; M.H. Mahmoud; Karam S. El-Nasser; Taha Abdel Mohaymen Taha (Heliyon, 2024)
This work describes the development of a novel fluorescence sensor based on magnesium/S@g-C3N4 nanosheets for selective detection of copper (Cu2+) ions in water. Mg/S@g-C3N4 nanosheets were prepared by the polycondensation technique and investigated by X-ray diffraction (XRD), ATR-FTIR spectroscopy, scanning electron microscopy (SEM), surface area (BET), and UV–Vis optical absorption measurements. XRD and ATR-FTIR analysis showed the characteristic peaks for S@g-C3N4. The broad full width at half maximum (0.056 radians) implies a smaller crystallite size, representing smaller Mg/S@g-C3N4 sheets. SEM micrograph showed non-exfoliated nanosheets with flake-like structures. The EDS mapping confirmed the presence of magnesium, carbon, nitrogen, and sulfur throughout the nanosheets. The Mg/S@g-C3N4 nanosheets possess a high surface area of 40 m2/g and mesopores within the nanosheets, with a size of 1.57 nm. The band gap of the Mg/S@g-C3N4 nanosheet was estimated to be 3.0 eV. The sensor exhibits a strong quenching response towards Cu2+ ions, with a decrease in fluorescence intensity as the concentration of Cu2+ increased from 1 μM to 20 μM. The Stern-Volmer quenching constant (KSV) showed a relatively high value of 185053 M−1. The estimated value of LOD by the Mg/S@g-C3N4 sensor for Cu2+ was 16.2 nM. The sensor offered high sensitivity and selectivity for Cu2+ detection over other heavy metals.